KIPIN SCHOOL DIGITAL LEARNING: SOLUTIONS TO INCREASE STUDENTS' READING INTEREST AND MOTIVATION - Paijan Rambe; Henri Yanto Daulay; Indah Wati; Wimbi Apriwanda Nursiwan; Aditya Warman; Shifa Khairunnisa (International Journal of Educational Best Practices, 2025)
This research is motivated by the low interest in reading among students in Riau Province, which demands the active role of all stakeholders in improving the quality of human resources, especially in the field of Education, one of which is collaboration with the government through digital literacy programs. One of them is the use of digital libraries such as the Kipin School application developed by the government to support reading interest and digital literacy. The purpose of this study is to describe and analyze the increase in students' reading interest and learning motivation through the use of the Kipin School at SMK Muhammadiyah Pekanbaru. The research method used is pre-experiment, with the aim of obtaining accurate data through the implementation of direct experiments on the research object. The results of the study showed that the use of Kipin School had a positive effect on students' reading interest and learning motivation. The results of the Paired Sample Test showed an increase in the average reading interest score from 59.71 (pretest) to 65.08 (posttest). This increase proved to be statistically significant, with a significance value of 0.000 (< 0.05) and a positive correlation of 0.736. Similarly, students' motivation to learn also improved, with the average score increasing from 57.32 to 63.28 after the intervention. The significance value of 0.000 (< 0.05) and the correlation of 0.823 confirm that the influence of Kipin School on learning motivation is very strong and this study concludes that digital learning through Kipin School is effective in increasing reading interest and learning motivation, so that it has the potential to be a solution in fostering a literacy culture among students. By implication, schools can use Kipin School as a modern learning tool to foster reading habits and integrate them into more interactive teaching strategies, and become a reference in the development of more advanced digital literacy programs.